Arterial stiffness measured by cardio‐ankle vascular index is greater in non‐obese young women with polycystic ovarian syndrome. Issue 2 (4th November 2020) - Kilic, Derya; Kilic, Ismail Dogu; Sevgican, Cihan Ilyas; Kilic, Oguz; Alatas, Erkan; Arslan, Muhammet; Avci, Esin; Guler, Tolga
Abstract: Aim: The association of metabolic abnormalities and polycystic ovarian syndrome (PCOS) has been documented, but few studies have focused on cardiovascular risk in these women. The aim of this study was to compare arterial stiffness by using the cardio‐ankle vascular index (CAVI) in PCOS women with controls, and to evaluate whether any clinical or laboratory variables had independent associations with it. Methods: A group of 160 women, matched for age and body mass index were recruited. Diagnosis of PCOS was made according to the Rotterdam criteria. Arterial stiffness using CAVI was evaluated in non‐obese young woman, with and without PCOS. Results: In the PCOS group ( n = 80), 60 cases (75%) had findings of hyperandrogenism, 59 (73.8%) had ovulatory dysfunction, and 70 (87.5%) had an ultrasonographic appearance of polycystic ovaries. Women with PCOS had significantly higher mean CAVI values when compared to subjects without PCOS (5.78 ± 0.64 vs 5.28 ± 0.77, P  < 0.001). Multiple regression analysis revealed that androgen excess was associated with increased arterial stiffness, independent of ovulatory dysfunction, polycystic ovaries, body mass index and age. Conclusion: This data suggests that vascular compliance is decreased in young women with PCOS. Androgen excess is independently associated with increased arterial stiffness.